2022
DOI: 10.1007/s10798-021-09724-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of design thinking in higher education: a multi-actor perspective on problem solving and creativity

Abstract: This study investigates the effects of using design thinking on students’ problem solving and creativity skills, applying a constructivist learning theory. A course where students use design thinking for analyzing real problems and proposing a solution, was evaluated. The study involved 910 novice university students from different disciplines who worked in teams throughout the semester. Data were collected at three times during the semester, i.e. at the beginning (t0), in the middle (t1) and at the end (t2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 66 publications
3
26
0
2
Order By: Relevance
“…It has been discovered that e-tutors outperform the average when it comes to learning how to assist students through the make prototype step of the design process in a virtual environment. The findings were in line with recent research by Guaman-Quintanilla, et al (2022), who found that facilitators in a design thinking course considerably improved their guide abilities as they progressed to the make prototype stage, where they show a lot of inventiveness. These findings were consistent with those of Koroglu and Yildiz (2021), who found that students had a good time, that brainstorming for the make prototype stage went smoothly, that they were able to determine the ultimate goal from their abilities, that they were able to determine the needs and solutions for the make prototype stage of the design process, and that they had a good time during the guidance, which was most entertaining.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It has been discovered that e-tutors outperform the average when it comes to learning how to assist students through the make prototype step of the design process in a virtual environment. The findings were in line with recent research by Guaman-Quintanilla, et al (2022), who found that facilitators in a design thinking course considerably improved their guide abilities as they progressed to the make prototype stage, where they show a lot of inventiveness. These findings were consistent with those of Koroglu and Yildiz (2021), who found that students had a good time, that brainstorming for the make prototype stage went smoothly, that they were able to determine the ultimate goal from their abilities, that they were able to determine the needs and solutions for the make prototype stage of the design process, and that they had a good time during the guidance, which was most entertaining.…”
Section: Discussionsupporting
confidence: 91%
“…Almaghaslah and Alsayari (2022) validated Yedra and Aguilar's findings that during the application of a software system for students with dyslexia towards the development of content levels for make prototypes, the students were able to interact with the playful application part, which gave them the option of interacting with the make prototype's playful activities. (Almaghaslah & Alsayari, 2022;Guaman-Quintanilla, et al, 2022;Koroglu & Yildiz, 2021;Yedra & Aguilar, 2022) it is determined that students benefited from the strategies that made unique demands on how the make prototype stage is taught, especially in a virtual environment. Furthermore, the findings of Colombelli, et al (2022) added to what was previously said, implying that students' perspectives regarding entrepreneurial education and the types of abilities gained from a make prototype program in which they participated were positively influenced.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most celebrated attributes of the DT is the fact of accepting the error, if it serves for a better construction of the proposal and the formative activity (Guaman-Quintanilla et al, 2022).…”
Section: Choosing a Strategy To Integrate Csr And The Sdgsmentioning
confidence: 99%
“…The understanding begins with purposely analyzing, defining, and redefining the problem with an empathetic approach, which includes logic and emotion to immerse in another person's context and to develop satisfiable and creative solutions (Abdulla et al. , 2020; Guaman-Quintanilla et al. , 2022; Rubenstein et al.…”
Section: Use Of Design Thinking In Higher Educationmentioning
confidence: 99%
“…In real-world problem-solving, the best solution is to approach another person's problems and develop a deep understanding of it with an empathetic view (Saidi, 2021). The understanding begins with purposely analyzing, defining, and redefining the problem with an empathetic approach, which includes logic and emotion to immerse in another person's context and to develop satisfiable and creative solutions (Abdulla et al, 2020;Guaman-Quintanilla et al, 2022;Rubenstein et al, 2020a, b). During the design thinking, the initial step is developing empathy with the actors involved in the problem, which stimulates insights, inspiration, and intuition (Glen et al, 2015a, b).…”
Section: Use Of Design Thinking In Higher Educationmentioning
confidence: 99%